Warranty and Maintainability Analysis for Sensor Embedded Remanufactured Products in Reverse Supply Chain Environment - Ammar Yahya Alqahtani; Surendra M. Gupta (International Journal of Supply Chain Management, 2017)
Remanufactured products are very popular with consumers due to their appeal to offer the latest technology with lower prices compared to brand new products. The quality of a remanufactured product induces hesitation for many consumers, in regards to its efficacy and reliability. One stratagem that remanufacturers could employ to encourage customer security are product warranties. This paper studies and scrutinizes the impact that would be had by offering renewing warranties on remanufactured products. This study was able to determine the optimal costs of warranty for two-dimensional non-renewable warranty offered on remanufactured products using the simulation model and design of experiments.